2009
DOI: 10.1007/s10719-008-9223-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of a sialoglycosylated bacterial ABC-type phosphate transporter protein from patients with visceral leishmaniasis

Abstract: We report the discovery and characterization of a glycosylated bacterial ABC-type phosphate transporter isolated from the peripheral blood mononuclear cell (PBMC) fraction of patients with visceral leishmaniasis (VL). Three disease-associated 9-O-acetylated sialoglycoproteins (9-O-AcSGPs) of 19, 56 and 65 kDa, respectively, had been identified and their purity, apparent mass and pI established by SDS-PAGE and isoelectric focusing. Western blot analyses showed that the 9-O-acetylated sialic acid is linked via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Furthermore, these antibodies, as reported earlier, are leishmanicidal in activity; that is, they are capable of triggering the classical complement pathway, thereby causing Leishmania cell death (5). Alternatively, several other 9-OAcSGPs have been documented on immune cells (65, 56, and 19 kDa) and erythrocytes (112, 107, 103, 57, 51, and 48 kDa) of VL patients (4,11,22). Since the alteration of sialic acid expression (via the alteration of enzymes responsible for sialic acid metabolism) has been well documented as a disease-induced phenomenon (26,48,49), the induction of these 9-OAcSGPs on the host cells of patients with active VL is possibly a result of parasitic infection.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Furthermore, these antibodies, as reported earlier, are leishmanicidal in activity; that is, they are capable of triggering the classical complement pathway, thereby causing Leishmania cell death (5). Alternatively, several other 9-OAcSGPs have been documented on immune cells (65, 56, and 19 kDa) and erythrocytes (112, 107, 103, 57, 51, and 48 kDa) of VL patients (4,11,22). Since the alteration of sialic acid expression (via the alteration of enzymes responsible for sialic acid metabolism) has been well documented as a disease-induced phenomenon (26,48,49), the induction of these 9-OAcSGPs on the host cells of patients with active VL is possibly a result of parasitic infection.…”
Section: Discussionmentioning
confidence: 70%
“…Since the alteration of sialic acid expression (via the alteration of enzymes responsible for sialic acid metabolism) has been well documented as a disease-induced phenomenon (26,48,49), the induction of these 9-OAcSGPs on the host cells of patients with active VL is possibly a result of parasitic infection. Importantly, previous studies have demonstrated that each of these 9-O-AcSGP molecules is different from the others at the protein level, as revealed in isoelectric-focusing studies by the presence of discrete bands indicating their molecular heterogeneity, even though they are all alike in having 9-O-AcSA on their terminal surface (22). Thus, anti-9-O-AcSGP antibodies driven by the 9-OAcSGPs present on the parasites recognize the diseaseassociated 9-O-AcSGPs on PBMC VL via recognition of the terminal 9-O-AcSA.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations